Blended Instruction And Cultural Principles Foster Elementary Digital Citizenship: Instruksi Campuran Dan Prinsip Budaya Membentuk Kewarganegaraan Digital Dasar - Nurul Aini; Raden Roro Nanik Setyowati; Akhwani Akhwani; Muhammad Rusli; Lalu Habiburrahman (Pedagogia : Jurnal Pendidikan, 2026)
General Background The rapid technological transformation significantly blurs the distinction between the physical and virtual worlds for young learners. Specific Background While modern technology provides numerous educational advantages, it concurrently exposes children to systemic threats, including unethical online behavior and cyber sexual violence. Knowledge Gap Despite recognizing online responsibility as a core competency, current educational frameworks predominantly utilize technocentric approaches, frequently neglecting essential affective dimensions and leaving educators unprepared for proactive risk mediation. Aims This systematic literature review synthesizes recent global and local research concerning academic management strategies, pedagogical models, and threat mitigation to establish a robust foundation for early education. Results Findings indicate that innovative instructional designs significantly cultivate positive attitudes and academic interest. Furthermore, active teacher mediation is crucial for mitigating cyber threats, while the integration of local philosophies, such as Pancasila, provides a necessary moral compass. Novelty The synthesis redefines the subject beyond mere technical proficiency, positioning it as a construct requiring moral agency, psychological resilience, and an ethics of care. Implications Achieving a secure and inclusive ecosystem necessitates comprehensive policies supporting professional development and future longitudinal research exploring artificial intelligence in ethical simulations. Highlights Active teacher mediation mitigates online risks including cyber threats and sexual violence. Integrating national philosophies establishes a vital moral compass for student behavior. Future academic frameworks necessitate artificial intelligence exploration for ethical simulation design. Keywords Character Education; Online Risk Mitigation; Systematic Literature Review; Ethics Of Care; Cyber Security